THE APPLICATION OF TEACHER ISLAMIC COMMUNICATION PRINCIPLES IN THE CHARACTER DEVELOPMENT OF VOCATIONAL HIGH SCHOOL STUDENTS IN THE CITY OF MEDAN - Rubino; Muhammad Zoel Akbar Syah (INFOKUM, 2022)
This study aims to determine the principles of Islamic communication to teachers in building the character of Medan vocational high school students. This research uses a type of qualitative research with a descriptive approach. Using qualitative data types in the form of primary data and secondary data. The data collection technique is in the form of observation and documentation. The results of this study indicate that the application of Islamic religious education in schools (public) in the city of Medan is less than optimal. The implementation of Islamic religious education in public schools for students is minimal if they only rely on their religious education from regular school hours. Except for students who live in areas where there are Madrasah Diniyah or Islamic boarding schools. The development of the soul experienced during puberty results in the conditions of religious life during puberty being easily shaken and doubts in faith, indecision and inner conflict begin to arise. The principle of Islamic communication can be applied through qaulan sadidan (true, not lying); qaulan baligha (straightforward, effective); qaulan ma'rufa (good and polite words); qaulan karima (respect, respect); qaulan layina (gentle); and qaulan maysura (easy to understand).